1988
DOI: 10.1093/jaoac/71.2.350
|View full text |Cite
|
Sign up to set email alerts
|

Liquid Chromatographic Determ [nation of Available Lysine in Soybean and Fish Meal

Abstract: A method for the determination of available lysine on the basis of the reactivity of the e-amino group with fluorodinitrobenzene (FDNB) has been optimized. Hydrolysis is performed in closed vessels in an autoclave. Conditions for different meals were established by using a modified sequential simplex method. Hydrolysis for 4 h was sufficient for the meals studied—soybean and fish. The use of liquid chromatography to determine available lysine was studied, and optimum conditions were established for separation … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
4
0

Year Published

1992
1992
2001
2001

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 0 publications
0
4
0
Order By: Relevance
“…A variety of different methods have been developed to determine available lysine (Carpenter, 1960;Booth, 1971;Kakade and Llener, 1969;Walker, 1979;Rabasseda et al, 1988). Even though there are drawbacks, the most widely used method was developed by Carpenter (1960) and modified by Booth (1971).…”
Section: Available Lysinementioning
confidence: 99%
See 1 more Smart Citation
“…A variety of different methods have been developed to determine available lysine (Carpenter, 1960;Booth, 1971;Kakade and Llener, 1969;Walker, 1979;Rabasseda et al, 1988). Even though there are drawbacks, the most widely used method was developed by Carpenter (1960) and modified by Booth (1971).…”
Section: Available Lysinementioning
confidence: 99%
“…The estimation of available lysine has been applied to plant protein (Joklnen et al, 1976;Rlnge and Love, 1988), animal protein (Carpenter, 1960), fish meal (Rabasseda et al, 1988) and soymllk (Van Buren et al, 1964;Hand et al, 1963). Wolf et al (1979) found that the FDNB method Off-colors in cheese and meats tire associated with poor flavor quality.…”
Section: Available Lysinementioning
confidence: 99%
“…5 Chromatographic techniques have been used to separate e-DNP-lysine from interfering amino acids and other compounds. 6 Available lysine was measured to evaluate the effect of heating on the protein quality of the following cereal products: pasta, 7 noodles, 8 breads 9 and cereal¯akes. 10 However, data is scarce on available lysine in processed infant cereals.…”
Section: Introductionmentioning
confidence: 99%
“…Some of these are long reaction times, requirements for heating, hydrolysis of proteins, HPLC amino acid analysis, solvent extraction, and variability of reaction medium for different proteins, difficult or dangerous reagents, or numerous manipulations of sample. Some of these problems are encountered in the most widely used procedures, which employ 1-fluoro-2,4-dinitrobenzene (Holguin and Nakai, 1980;Peterson and Warthesen, 1979;Rabasseda et al, 1988). Furthermore, several researchers have reported substantial differences in results obtained with various methods (Acquistucci et al, 1987;Anderson, and Erbersdobler, 1982;Hegedus et al, 1982;Ostrowski-Meissner, 1980).…”
Section: Introductionmentioning
confidence: 99%